Specimens of Thylacinus cynocephalus in collections of the Czech Republic (Mammalia: Thylacinidae) - Robovský, Jan; Sleightholme, S.; Vohralík, Vladimír; Benda, Petr (Národní muzeum v Praze, 2015)
A list of the thylacine specimens housed in collections of the Czech Republic is given and all available data on the specimens are provided, including the photographs. One mounted skin is in the National Museum Prague and one complete skull in the private Zoological Museum Protivín. Four pouch juveniles (liquid specimens) of the estimated age of two weeks are housed at the Department of Zoology, Charles University, Prague.
Keywords: Collections, marsupials, thylacine, Tasmanian tiger